Modelling and Environmental Assessment of Heterogeneous Catalysis Biodiesel Process Using War Algorithm - As Eleyana, Ali (2013)
Environmental assessment in a preliminary designing stage of a process is important to evaluate the environmental friendliness of a process design, minimizing the environmental impact of the process. WAR algorithm, a methodology for determining the potential environmental impact (PEI) of a chemical process is developed to describe the flow and the generation of PEI through a chemical process. WAR algorithm which acts as a comparison tool in selecting the environmentally benign design option is developed using heterogeneous catalysis and alkali homogeneous catalysis of biodiesel process as case study. Heterogeneous catalysis of biodiesel process flowsheeting is first developed and simulated using Aspen Plus 7.0. Data and simulation results are then exported to the spreadsheet for environmental assessment of WAR algorithm. Four PEI indexes (TRO,TOP,TRG,TGP) are used to evaluate the environmental friendliness of a process design while eight PEI categories (four global and four toxilogical) are used to evaluate the PEI indexes. Comparison of the PEI indexes concluded that heterogeneous catalysis of biodiesel process showed more environmentally friendly process with minimum amount of PEI value compared to homogeneous catalysis process.